2018
DOI: 10.1590/1982-0194201800065
|View full text |Cite
|
Sign up to set email alerts
|

Fatores de risco para transtornos alimentares em graduandos de enfermagem

Abstract: Objective: To identify the presence of risk factors in nursing students for the development of eating disorders. Methods: Cross-sectional study with undergraduate nursing students from a public university, where a demographic questionnaire, the Eating Attitude Test (EAT), and the Body Shape Questionnaire (BSQ) were used. Descriptive analysis, Pearson's correlation and linear regression were used to analyze the data. Results: Among the 120 undergraduate students, 30 (25%) presented altered eating behavior, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 19 publications
3
7
0
7
Order By: Relevance
“…Some studies with undergraduate health sciences students have shown that high BMI values tend to predict a higher level of body dissatisfaction. (24,26,(30)(31)(32)(33)(34)(35) This result was also found in this study, and the individuals classified as overweight were the most dissatisfied with their body image, including two volunteers with severe body dissatisfaction. Kakeshita et al, (34) in their study with undergraduate students in the city of Ribeirão Preto (SP), also showed overweight volunteers were the most dissatisfied, but this finding differs from that of Kesller al., (36) who found the highest BSQ means in normal weight individuals.…”
Section: ❚ Discussionsupporting
confidence: 86%
“…Some studies with undergraduate health sciences students have shown that high BMI values tend to predict a higher level of body dissatisfaction. (24,26,(30)(31)(32)(33)(34)(35) This result was also found in this study, and the individuals classified as overweight were the most dissatisfied with their body image, including two volunteers with severe body dissatisfaction. Kakeshita et al, (34) in their study with undergraduate students in the city of Ribeirão Preto (SP), also showed overweight volunteers were the most dissatisfied, but this finding differs from that of Kesller al., (36) who found the highest BSQ means in normal weight individuals.…”
Section: ❚ Discussionsupporting
confidence: 86%
“…Research has demonstrated that post-secondary students experience a variety of mental illnesses such as depression (Tung et al, 2018), bipolar disorder (Kennedy et al, 2005;Thornton, 2016), eating disorders (Eisenberg et al, 2011;Mazzaia & Santos, 2018), and addiction (Cicolini et al, 2018;Lamberti et al, 2017;Parel & Thomas, 2017). Nursing students may be predisposed to the development of MI given the social, emotional, and intellectual demands of nursing education, in conjunction with their personal, familial, and social situations (Birks et al, 2009;Burnard et al, 2007;Facundes & Ludermir, 2005;Sharma & Kapur, 2011).…”
Section: Anxiety and Mental Illnessmentioning
confidence: 99%
“…Estudos com universitários de nutrição, enfermagem, educação física e medicina verificaram que estes grupos apresentaram evidências de comportamentos de risco para TAs. 5,6 O fato desse grupo sofrer com maiores cobranças em relação a sua forma física o torna suscetível ao desenvolvimento de distúrbios de imagem e comportamentos alimentares inadequados. 7 A revisão integrativa realizada por Nunes políticas públicas e projetos no âmbito universitário para a prevenção de distorção de imagem corporal e de transtornos alimentares.…”
Section: Introductionunclassified